Six native churches: a preliminary survey of religion in an urban location - Hammond-Tooke, W D (Social Anthropology, 2020)
This report had its genesis in a proposed thesis, purporting to investigate the part that Religion (including both Christianity and the indigenous beliefs of the Bantu) is playing in the lives of the people at Langa, the Municipal Native location lying about eight miles from Cape Town. It was felt that, after some two hundred years of missionary endeavour in South Africa, the time was ripe for an assessment of the degree to which Christianity had become part of the Bantu scheme of things, to see how far it has changed the culture and outlook of the people, and how far it, in its turn, has been modified by the ever-menacing mass of Africa heathendom. It was hoped that the finished work would be of use, not only yo students of sociology, but also to the practical man on the mission-field who so often, working hard in his corner of the vineyard, has no opportunity to estimate what effects his labour is having on the bulk of the people.